Теоретико-методичні аспекти професійної підготовки робітників лісогосподарського профілю в Австрії - Подоляк, Зоряна (Studies in Comparative Education, 2015)
У статті розглянуто теорію і практику підготовки робітничих кадрів для лісогосподарської галузі в Австрії. Проаналізовано нормативно-правові основи функціонування австрійських лісогосподарських шкіл, що забезпечують професійну освіту робітників лісового господарства, висвітлено її змістові, організаційні, методичні аспекти. Схарактеризовано основні напрями реформування закладів професійної підготовки робітничих кадрів лісогосподарської галузі в Австрії. В статье рассмотрены теория и практика подготовки рабочих кадров для лесохозяйственной отрасли в Австрии. Проанализированы нормативно-правовые основы функционирования австрийских лесохозяйственных школ, обеспечивающих профессиональное образование работников лесного хозяйства, освещены ее содержательные, организационные, методические аспекты. Охарактеризованы основные направления реформирования учреждений профессиональной подготовки рабочих кадров лесохозяйственной отрасли в Австрии. The topicality of the article has been defined by a general need of Ukrainian forest staff supply qualitative modernization, realization of sweeping forestry reforms and wood processing industry education with the aim of framework conditions organization for the forest workers’ training in individual, based on knowledge forest planning and management of ecological forest use and all these ecosystems function preservation. Its objective is to outline the foreign experience, in particular, the Austrian one on the above-mentioned problems solving, that has a great scientific and practical value, though hasn’t been researched in Ukrainian literature yet. According to the determined problem and objective of the article the theory and practice of forest workers’ vocational training in Austria have been dealt; the legal bases of the Austrian forestry school functioning have been analyzed; the aspects of content, organization of their educational work have been revealed; the urgent problems have been identified and the main tendencies of forestry education system modernization in Austria have been characterized. Further research works will deal with the analysis of theory and practice of forest staff training in higher education system in Austria and study of the Austrian state system of forest workers’ certification.